2019
DOI: 10.1002/joc.6012
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and synoptic analyses of offshore wind variations

Abstract: In this study, variations of offshore wind speed in the northern and central coasts of British Columbia are examined using wind observations from nine buoys distributed in the region. Wind speeds from all buoys are extrapolated to the standard (10 m) wind measurement height as well as to the wind turbine hub height (100 m) using Monin–Obukhov similarity theory. Sustained winds above several thresholds are analysed and values of 50 and 100‐year return extreme wind speed levels are calculated for all locations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
(81 reference statements)
4
3
0
Order By: Relevance
“…Wind over the SoG is determined by the synoptic-scale meteorology of the northeastern Pacific Ocean. Consistent groupings of three dominant synoptic types have resulted from cluster analyses of meteorological data at marine (Bakri and Jackson, 2019) and land-based (Stahl et al, 2006) ob- Relevant geographic features, meteorological observing platforms (magenta symbols) and the subdomain used for principal component analysis (red box) referenced in this study are also shown. Coastline data were obtained from the GSHHS database (Wessel and Smith, 1996).…”
Section: Study Areasupporting
confidence: 65%
See 2 more Smart Citations
“…Wind over the SoG is determined by the synoptic-scale meteorology of the northeastern Pacific Ocean. Consistent groupings of three dominant synoptic types have resulted from cluster analyses of meteorological data at marine (Bakri and Jackson, 2019) and land-based (Stahl et al, 2006) ob- Relevant geographic features, meteorological observing platforms (magenta symbols) and the subdomain used for principal component analysis (red box) referenced in this study are also shown. Coastline data were obtained from the GSHHS database (Wessel and Smith, 1996).…”
Section: Study Areasupporting
confidence: 65%
“…These types can be summarized as (1) a summer type with a pronounced North Pacific High and northwesterly, along-isobar wind at the coast, (2) a winter type with a pronounced Aleutian Low and strong southeasterly, cross-isobar wind at the coast, and (3) a transition type between the two pressure centers that dominates during the shoulder seasons. The strongest observed winds at marine locations are associated almost exclusively with the winter synoptic types, and spatial variability between locations is consistent with the presence of extratropical cyclones (Bakri and Jackson, 2019). Conversely, summer synoptic types are weaker but more persistent than winter types in terms of their recurrence probability, and they are also generally longer lived, with a maximum duration of 15-20 d relative to the shorter 5-10 d maximum of the winter types (Stahl et al, 2006).…”
Section: Study Areasupporting
confidence: 58%
See 1 more Smart Citation
“…The topographic complexity and glacial history of BC's coastline, that likely influence species distributions (Pielou, 1991), creates unique challenges for modeling and as a result nearshore connectivity is poorly understood. In this region, there are also two important climatic changes that drive strong seasonal differences in hydrodynamics and have ecological relevance: (1) the spring transition between Aleutian Low and North Pacific High pressure dominance over the northeast Pacific that suppresses winter storm activity resulting in phytoplankton blooms (Kathleen Collins et al, 2009;Bakri and Jackson, 2019), and (2) the summer freshet, dominated by the undammed Fraser River that increases the stratification and reduces the residence time of the surface layer (Pawlowicz et al, 2007).…”
Section: Study Systemmentioning
confidence: 99%
“…The importance of wind in controlling productivity is well established. During the transition from winter to spring, the expansion of the North Pacific High suppresses winter storm activity in the region (Bakri and Jackson, 2019). Calm winds and clear skies provide light and stratification for a spring phytoplankton bloom to occur (Collins et al, 2009).…”
Section: Introductionmentioning
confidence: 99%